Employee Performance as Determined by the Implementation of Compensation and Job Satisfaction; Moderation in Leadership Style (Jurnal Manajemen Bisnis, 2022)
In industrial-organizational psychology, one of the most important things to study is the link between pay and performance. In the era of public management, performance measurement based on output and remuneration systems became a necessity for public sector organizations in many countries. For this reason, in accommodating previous studies while presenting novelty, we try to jointly test the satisfaction construct at work as a predictor in shaping performance. The survey was given to employees and distributed, and primary data was collected by randomly distributing research questionnaires. Through the technique of sampling judgment, eighty-seven employees were determined to be respondents. Based on the results of the PLS-SEM test, the remuneration construct, leadership style, and job satisfaction have a positive and significant effect on employee performance. Implementation of remuneration and job satisfaction were also found to have a significant effect on employee performance. According to the moderator proposed in this study, job satisfaction was found to strengthen the direct relationship to performance. Theoretical and practical implications and suggestions for future research are further elaborated.